2016
DOI: 10.1007/s13142-016-0438-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of SmokeFree Baby: a smoking cessation smartphone app for pregnant smokers

Abstract: Pregnant smokers may benefit from digital smoking cessation interventions, but few have been designed for this population. The aim was to transparently report the development of a smartphone app designed to aid smoking cessation during pregnancy. The development of a smartphone app (‘SmokeFree Baby’) to help pregnant women stop smoking was guided by frameworks for developing complex interventions, including the Medical Research Council (MRC), Multiphase Optimization Strategy (MOST) and Behaviour Change Wheel (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 51 publications
0
54
0
Order By: Relevance
“…There is some evidence of potential publication bias in this review, indicated by forest plot asymmetry, possibly due to the inclusion of several pilot studies with small sample sizes. Given the rapid advance in technology over the last decade, it is likely that the addition of trials which are currently in progress, for example, the development of SmokeFree Baby (Tombor et al, 2016), will decrease any uncertainty about the effectiveness of digital interventions. It remains important, however, to explore the content of older, more dated technological interventions to assess what can be improved upon with the use of the latest technology.…”
Section: Limitationsmentioning
confidence: 99%
“…There is some evidence of potential publication bias in this review, indicated by forest plot asymmetry, possibly due to the inclusion of several pilot studies with small sample sizes. Given the rapid advance in technology over the last decade, it is likely that the addition of trials which are currently in progress, for example, the development of SmokeFree Baby (Tombor et al, 2016), will decrease any uncertainty about the effectiveness of digital interventions. It remains important, however, to explore the content of older, more dated technological interventions to assess what can be improved upon with the use of the latest technology.…”
Section: Limitationsmentioning
confidence: 99%
“…Lastly, use of the Behaviour Change Wheel (BCW) 74 should be considered in intervention development, as is being done in related fields of research. 75 The BCW is a theory-and evidence-based tool which draws on a range of theoretical approaches to address the target behaviour of interest and has the potential to lead to more effective interventions 74 .…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…personal life information or substance abuse), as well as the integration of simple applications in midwives' everyday practice, including digital applications or conventional tools like printed screening questionnaires, decision trees, and checklists. These would enable midwives to conduct the smoking and alcohol use screening more efficiently and to set quitting goals and behavior change interventions in a more structured way [29][30][31].…”
Section: Discussionmentioning
confidence: 99%